2010
DOI: 10.5194/acp-10-6461-2010
|View full text |Cite
|
Sign up to set email alerts
|

A multi-decadal history of biomass burning plume heights identified using aerosol index measurements

Abstract: Abstract.We have quantified the relationship between Aerosol Index (AI) measurements and plume height for young biomass burning plumes using coincident Ozone Monitoring Instrument (OMI) and Cloud-Aerosol Lidar and Infrared Pathfinder Satellite Observations (CALIPSO) measurements. This linear relationship allows the determination of high-altitude plumes wherever AI data are available, and it provides a data set for validating global fire plume heights in chemistry transport models. We find that all plumes detec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
78
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(82 citation statements)
references
References 51 publications
(57 reference statements)
4
78
0
Order By: Relevance
“…Pyro-convection during forest fires can inject particles into the UT/LMS. However such events are not frequent and none one of the events identified in Guan et al (2010) coincides with the eruptions studied here. Also no clearly elevated concentrations of K in excess of the ash concentration are seen in the samples, which would be expected from fires (Andreae et al, 1998).…”
Section: Carbonaceous Aerosol In Volcanic Cloudsmentioning
confidence: 48%
See 1 more Smart Citation
“…Pyro-convection during forest fires can inject particles into the UT/LMS. However such events are not frequent and none one of the events identified in Guan et al (2010) coincides with the eruptions studied here. Also no clearly elevated concentrations of K in excess of the ash concentration are seen in the samples, which would be expected from fires (Andreae et al, 1998).…”
Section: Carbonaceous Aerosol In Volcanic Cloudsmentioning
confidence: 48%
“…Especially aerosol from forest fires can be brought to high altitudes by extreme convection, however, the frequency and global contribution of such events is poorly understood (Fromm et al, 2004(Fromm et al, , 2008. Guan et al (2010) estimated that on average about six such events per year lead to injection of particles to altitudes above 8 km. With a frequency of one or a few events per year, volcanic eruptions contribute to stratospheric aerosol mass of similar magnitude as OCS does , and in a few events per century volcanism is by far the strongest source of stratospheric aerosol (Ammann et al, 2003).…”
mentioning
confidence: 99%
“…Thick clouds obscure underlying UVbackscattering layers (Penning de Vries and Wagner, 2011), hence the enhanced AI here means the smoke is mixed with or situated above deep, opaque cloud tops. Double-digit AI values have been shown to be indicative of optically dense, high-altitude smoke plumes (Guan et al, 2010;Fromm et al, 2010). Hence the OMI AI and MODIS visible plus MODIS BT together indicate a substantial mass of smoke aerosols in the uppermost troposphere and tropopause region, injected by the Wollemi pyroCb.…”
Section: Novembermentioning
confidence: 98%
“…The AI is strategic for identifying smoke plumes in all background conditions including land, sea, even cloud. Guan et al (2010) have shown how the AI is used strategically for smoke-plume analyses. A-Train radar and lidar data used here are native 94 GHz reflectivity and attenuated 532 nm attenuated backscatter, respectively, as described in Mace et al (2006) and Vaughan et al (2004).…”
Section: Datamentioning
confidence: 99%
“…Plume heights have been related to plume optical properties in both the tropics and extratropics: Guan et al (2010) found that for plumes less than 2 days old, plume height was strongly correlated with aerosol index, a measurement of the contribution of aerosols to UV scattering. Tosca et al (2011) characterize the seasonal and interannual distribution of occurrence, height, fire radiative power, and relationship to rainfall of fire-generated smoke plumes and clouds on Borneo and Sumatra from [2001][2002][2003][2004][2005][2006][2007][2008][2009].…”
mentioning
confidence: 99%